IMPROVEMENTS OF SCHOOL DEMONSTRATION EXPERIMENT BASED ON GAS-LIGHT TRANSFORMER ТГ 1020 (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article is devoted to the problem of formation and development of scientific concepts of schoolchildren the article discusses the concept of formation of the state of substance based on the principle of operation of a gas-light transformer.
Keywords: scientific concepts, properties of matter, the formation and development of concepts, the state of substance, gas light transformer.